Burnout and its impact on Nurses and Doctors - Zahra Tharani; Abeer Musaddique; Qutb, Syeda Humera (Journal of the Pakistan Medical Association, 2023)
Burnout is a highly researched syndrome resulting from job stress. It is an ultimate response that occurs because of chronic exposure to stressors from the job characterised by the magnitudes/key dimensions which are feeling of cynicism, sense of ineffectiveness, detachment from the job, lack of accomplishment and overwhelming exhaustion.1 This implies that burnout characterised by a variety of factors can cause extreme suffering to an individual. Exhaustion is a central quality of burnout and the most obvious manifestation of this complex syndrome. It refers to feelings of being overextended and depleted on one’s emotional and physical resources. The individual feels drained due to perpetual lack of energy as a result of which, the quality of work responsibility is compromised. The major sources of this exhaustion are work overload and personal conflicts at the work place. The cynicism dimension represents the interpersonal context that refers to negative, callous, or excessively detached response to various aspects of the job which results in the loss if idealism and dehumanisation of others. The inefficacy dimension represents the self-evaluation component of burnout that refers to feeling of incompetence and lack of achievement and productivity in work. Burnout is a cumulative reaction on ongoing occupational stressors. Healthcare professionals, especially clinicians seem to be at particular risk for burnout. Additionally nurses, specifically psychiatric nurses are considered as a group at risk for excessive stress and burnout because they are in constant interaction and frequent interpersonal contact with psychiatric clients and their families.2 These reasons and risk factors can be same in between the professions, however, even within the discipline there are gender differences that calls for further discussions. Continue...